The role of songs in first-graders’ oral communication development in english (2014)
We report on an action research project aimed at developing oral communication in first-graders, using songs as a strategy for young learners to use and enjoy English. It was developed at a Colombian public school over three months. The teacher-researchers attempted to encourage students using simple and amusing songs to help them learn new vocabulary in English and develop oral skills from the very moment they began their literacy process. In this article, we attempt to share our findings obtained from data collected through direct observation, field notes, video recordings, and interviews that show the process followed by very young learners to acquire vocabulary by singing.Reportamos un proyecto de investigación cuyo objetivo era desarrollar habilidades en la comunicación oral en niños de primero de primaria, a partir del empleo de canciones como estrategia para usar y disfrutar el inglés. El estudio se llevó a cabo en un colegio público colombiano, durante tres meses. Las docentes-investigadoras trataron de motivar a los estudiantes con canciones sencillas y divertidas para ayudarlos a aprender nuevo vocabulario en inglés, a la vez que desarrollaban destrezas orales en la lengua inglesa desde el inicio de su proceso de alfabetización. En este artículo compartimos los hallazgos provenientes de los datos recogidos a través de observación directa, notas de campo, grabaciones de vídeo y entrevistas, que muestran el proceso seguido por los jóvenes estudiantes al adquirir vocabulario cantando.